Devising a method for determining the moisture conductivity coefficient of subgrade soils taking into account European approaches and standards - Bubela, Andrii; Bondarenko, Liudmyla; Kvatadze, Yevheniia; Stozhka, Vitalii; Ivko, Andrii (Eastern-European Journal of Enterprise Technologies, 2024)
The object of this study is the theoretical and methodological approaches to determining the coefficient of moisture conductivity of subgrade soils. The work focuses on considering the European approaches and standards when devising a method for determining the coefficient of moisture conductivity of soils. In the course of the research, a method was developed for determining the coefficient of moisture conductivity of soils K1, which characterizes the diffusion movement of water, through the filtration coefficient K0, calculated in accordance with European requirements based on laboratory test data. The proposed method is based on a mathematical model built on the basis of the differential equation of changes in soil moisture. The model is special in that, unlike existing ones, the movement of water was modeled from the bottom up, which reflects the process of moisture accumulation in the lower layers of the subgrade from groundwater or topwater. A good agreement of the mathematical model with the data by other authors was obtained (the relative error did not exceed 12.98 %). A direct relationship between the moisture conductivity coefficient of soils K1 and their initial moisture content W0 and an inverse relationship between K1 and the total moisture capacity of soils WFH were established in the paper. Dependences were derived in the range of changes in initial soil moisture W0 from 0.08 to 0.15 and WFH from 0.15 to 0.5. It was found that the values of the moisture conductivity coefficient of soils K1 increase from 4.64·10-6 to 3.81·10-5 m2/h with an increase in their initial moisture content and with a decrease in total moisture capacity. From the point of view of engineering practice of road construction, the proposed method makes it possible to predict seasonal changes in soil moisture in the subgrade, to determine the strength of the road structure. This makes it possible to make sound design decisions on the installation of drainage systems on roads in order to extend their service life